Phenotypic and functional evaluations of peripheral blood monocytes from chronic-form paracoccidioidomycosis patients before and after treatment - Venturini, James [UNESP]; Cavalcante, Ricardo Souza [UNESP]; Golim, Marjorie de Assis [UNESP]; Marchetti, Camila Martins [UNESP]; Azevedo, Priscila Zacarias de [UNESP]; Amorim, Barbara Casella [UNESP]; Arruda, Maria Sueli Parreira de [UNESP]; Mendes, Rinaldo Poncio [UNESP] (Biomed Central Ltd, 2014)
Background: Paracoccidioidomycosis (PCM) is systemic mycosis caused by the thermal dimorphic fungus of genus Paracoccidioides, leading to either acute/subacute (AF) or chronic (CF) clinical forms. Numerous CF patients after treatment exhibit sequels, such as pulmonary and adrenal fibrosis. Monocytes are cells that are involved in the inflammatory response during active infection as well as in the fibrogenesis. These cells comprise a heterogeneous population with distinct phenotypic and functional activities. The scope of this study was to identify changes regarding functional and phenotypical aspects in monocytes comparing CF PCM patients on antifungal treatment versus non-treated patients (PMC-p).Methods: Twenty-three CF PCM composed of 11 non-treated patients (NTG) and 12 patients in apparent cure (ACG) were studied. Sixteen healthy individuals were used as control group (CG). Monocyte subsets were determined by immunophenotyping based on CD14 and CD16 expression. Cellular function was measured in vitro with and without stimulation with lipopolysaccharide (LPS) and P. brasiliensis exoantigen (PbAg) for 24 hours. Independent samples were compared using unpaired t tests, dependent samples were analyzed by paired t-test. Groups of more than two independent samples were analyzed using an ANOVA, with Tukey's post-test. Significance was set up at p < 0.05.Results: Our results showed high counts of peripheral blood CD14(+)CD16(+) and CD14(+)CD16(++) monocytes in untreated PCM-p accompanied by intense production of pro-inflammatory cytokines (IL-1 beta and TNF-alpha) and profibrotic growth factors (TGF-beta 1 and bFGF) by monocytes challenged with P. brasiliensis antigens. After the introduction of antifungal therapy, the counts of CD14(+)CD16(+) cells returned to baseline while CD14(+)CD16(++) counts remained high. Interestingly, counts of CD14(+)CD16(++) monocytes remained elevated even 52 +/- 7 months after successful antifungal treatment. Furthermore, the ACG-patients showed preserved pro-inflammatory activity in the presence of specific antigen stimuli and high spontaneous production of TNF-a by monocytes.Conclusions: Infection with Paracoccidioides leads to initiation of a specific proinflammatory response by monocytes of PCM-p during active disease and in the apparent cure. A profibrotic profile by monocytes was observed only at admission. Furthermore, PCM-p with apparent cure showed high spontaneous production of TNF-alpha and high counts of CD14(+)CD16(++) monocytes, probably induced by hypoxia duo to fibrotic sequelae.
Keywords: Paracoccidioidomycosis; Monocyte subsets; Pulmonary fibrosis; Antifungal therapy